At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
For the first one I did use the formula: p=2l+2w
if the perimeter= 64 units with the width y=11 units then; length=(p/2)width so, x=(p/2)y substituting those values we get x= (64/2)(11) x=?
x = 352 ?
Maybe I was doing it wrong when I was doing the formula: p=2l*2w 64=(2*20)*(2*11) 40 * 22 40*22 = 880
Yeah, I still don't understand how you received 352. I'm sorry. :(
I don't disregard that your answer is wrong, I just can't comprehend it. Maybe another way of explaining it?
i made a mistake it shd be p=2(l+w) and we want ''l'' so divide both side by 2 we get p/2=l+w now take away w from both sides wee get (p/2)-w=l
so substituting into that we get (64/2)-11=length
Ah. Okay, now I can see it. I was so focused on trying to use the length that was provided, that it was incorrect. Thank you.
Could you help me on my other question if you have time?
for the second question -4(x+1)-3=-3(x-4)...just making sure its this ..see u wrote (x-1) when u started it..
Ops, yeah its (x+1) sorry typo
The second step would start out like this: -4x+-4-3=-3x-12 I know that you need to get all the variables on one side of the equation, preferable the left side.
ok so -4(x+1)-3=-3(x-4) we can start by multiplying out parentheses so -4x-4-3=-3x+12 simplify -4x-7=-3x+12 add (3x) and (7) to boh sides we get -4x+3x=12+7 simplify -x=19 then divide by -1 x=-19
Okay: You would finally have -1x-7=12 then adding the seven to both sides of the equation. Finally you would have -1x=19 divide -1x by both sides and get x = -19 Ah, I see the mistake on my part, but thank you so much for your time.
Have a nice night, thank you again! @ LynFran I made sure I gave you a metal.
ok... welcome ...